2014
DOI: 10.1002/jez.1866
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of VIP and distribution of VIP/VPACR system in the testis ofPodarcis sicula

Abstract: Using molecular, biochemical, and cytological tools, we studied the nucleotide and the deduced amino acid sequence of PHI/VIP and the distribution of VIP/VPAC receptor system in the testis of the Italian wall lizard Podarcis sicula to evaluate the involvement of such a neuropeptide in the spermatogenesis control. We demonstrated that (1) Podarcis sicula VIP had a high identity with other vertebrate VIP sequences, (2) differently from mammals, VIP was synthesized directly in the testis, and (3) VIP and its rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…Five‐micrometer thick sections of Bouin‐fixed ovary were placed on polylysine glass slides (Menzel‐Glaser, Braunschweig, Germany), dewaxed and rehydrated. The sections were treated as previously reported (Agnese et al, , , b, , b; Rosati et al, , , 2017; Prisco et al, ) with 10 mM citrate buffer pH 6.0 in a microwave for antigen retrieval and then incubated in 2.5% H 2 O 2 in methanol for endogenous peroxidase blocking. Nonspecific background was reduced using normal goat serum (Pierce, Rockford, IL), 1 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Five‐micrometer thick sections of Bouin‐fixed ovary were placed on polylysine glass slides (Menzel‐Glaser, Braunschweig, Germany), dewaxed and rehydrated. The sections were treated as previously reported (Agnese et al, , , b, , b; Rosati et al, , , 2017; Prisco et al, ) with 10 mM citrate buffer pH 6.0 in a microwave for antigen retrieval and then incubated in 2.5% H 2 O 2 in methanol for endogenous peroxidase blocking. Nonspecific background was reduced using normal goat serum (Pierce, Rockford, IL), 1 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…For each reproductive period, ovaries of three different animals were collected and total RNA extracted using TRI‐Reagent (Sigma‐Aldrich, St. Louis, MO) according to the manufacturer's instructions and was evaluated by 1% agarose gel electrophoresis. RNA concentration was measured by determination of absorbance at 260 nm as previously reported (Agnese, Rosati, Prisco, et al, ; Agnese, Rosati, Coraggio, Valiante, & Prisco, ; Coscia, Simoniello, Giacomelli, Oreste, & Motta, ; Rosati et al, ). The RNA was then reverse‐transcribed with QuantiTect Reverse Transcription kit (Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover in the lizard, Podarcis sicula , more recently we have demonstrated a different localization of StAR, 3β‐HSD, 17β‐HSD, and 5α‐Red (Rosati, Santillo, et al, ) as well as a different expression and localization of P450 arom (Rosati, Agnese, et al, ), during spermatogenic cycle. This data suggested that, in P. sicula , the specific steroidogenic enzymes, together to other local factors as, pituitary adenylate cyclase activating peptide (PACAP; Rosati, Agnese, et al, ; Rosati et al, ) and vasoactive Intestinal Peptide (VIP; Agnese, Rosati, Coraggio, Valiante, & Prisco et al, ; Agnese et al, ; Rosati, Andreuccetti, et al, ; Rosati et al, ), could control the lizard testis activity. Also in the birds, in particular in zebra finches, were investigated the expression of the sex steroid‐synthesizing enzymes CYP11A1, 3β‐HSD, CYP17, and CYP19 in gonads and adrenals of animal adults (Freking, Nazairians, & Schlinger, ); in the details the authors showed that the ovaries but not the testis may secrete estrogen developmentally and the adrenals may contribute precursors for gonadal steroidogensis.…”
Section: Introductionmentioning
confidence: 98%